INVESTIGATING THE INFLUENCE OF AUTHORITARIAN LEADERSHIP AND SUPERVISOR SATISFACTION ON TURNOVER INTENTION: THE MODERATING ROLE OF EMPLOYEE UPBRINGING - Ting En, Hsiung; Tong Ming, Chong; Zhi Lin, Tan; Po Hung, Chen (PEOPLE: International Journal of Social Sciences, 2024)
Authoritarian leadership is prevalent in the Asian region, and previous research has found a positive correlation between authoritarian leadership and employees’ intention to leave their jobs. However, there are employees in the workplace who can adapt to such supervisors. Therefore, we approach this study from the perspective of "fit theory" to explore whether employees with authoritarian family upbringing can match with authoritarian leadership. This study aims to investigate the impact of authoritarian leadership on employees’ intention to leave, with supervisor satisfaction as the mediator and employees’ authoritarian family upbringing as the moderator. A total of 232 valid questionnaires were collected in this study. The results revealed that the level of authoritarian family upbringing among employees has a moderating effect on the relationship between authoritarian leadership and supervisor satisfaction.